The benefits of irrigation in mitigating the impacts of drought - Schluntz, Larry J., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
A few comments regarding the economic impacts of drought are made, then a model of a livestock ranch with and without irrigation is presented. The hypothesis is that irrigation reduces risk and stabilizes production of roughage, consequently there is better utilization of the cow herd and associated production factors. A dynamic linear programming model was constructed which captured the variations in yields and prices over time. Results verified that irrigation has a positive impact on income for ranchers, and a dynamic model more accurately simulates these impacts than a static model.
USCID regional meetings -- 1989
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.